ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. A DI KLINIK PRATAMA KAYU JATI TEMBILAHAN TAHUN 2022 - Yasmi, Yuli (STIKES HUSADA GEMILANG, 2023)
Comprehensive midwifery care is defined as care starting from pregnancy, childbirth, infant care, postpartum, and family planning (KB). In Inhil it is estimated that in 2020 the number of maternal deaths is 10 people and the number of infant deaths is 24 people. At the Klinik Kayu Jati Pratama, starting from April-December 2021, 44 pregnant women were recorded, 4 mothers gave birth, 4 postpartum mothers, 4 BBL and 39 family planning acceptors. The purpose of this care is to be able to provide comprehensive midwifery care to Mrs